Ritualization as Alternative Approach to the Spiritual Dimension of Palliative Care: A Concept Analysis - van der Weegen, Kim (Journal of religion and health, 2019)
The spiritual dimension is considered to be a central component of palliative care. However, healthcare professionals have difficulties incorporating the spiritual dimension into their everyday practice. We propose a new approach by looking beyond the mere functionality of care practices. Rituals and ritualized practices can serve to express and communicate meanings and values. This article explores how ritualized practices have the ability to open up space for the spiritual dimension of care in the context of palliative care.